A COMPLEMENT-FIXATION TECHNIQUE FOR FOOT- AND -MOUTH DISEASE AND VESICULAR STOMATITIS - LEVINE, JM; GIRON TELLEZ, A; EICHHORN, E A; CAMARGO, FERNANDO (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
This technic is highly accurate, easy to manipulate, and permits the analysis of a large number of specimens daily It permits a rapid, economic, accurate, serologic differentiation between foot-and-mouth disease and vesicular stomatitis virus and between
J AM VET MED ASSOC
Keywords: COMPLEMENT-FIXATION, TECHNIQUE, VESICULAR, STOMATITIS; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA